A structural equations model of job disengagement from the constructs of organizational justice, job satisfaction, innovation and trust in the era of industry 5.0 - Galván Vela, Esthela; Ravina-Ripoll, Rafael; Tobar-Pesántez, Luis Bayardo (My University, 2021)
Employees play a vital role in the results of companies, which is why the study of elements of the company's behaviour and climate is necessary for the retention of human talent. This study aims to identify the influence of perceived fairness, job satisfaction, support for innovation and trust on employee turnover and the relationship between these variables. In order to achieve this objective, a quantitative methodological design was carried out. A questionnaire was administered to 555 employees of a food industry company in northwestern Mexico. This instrument was validated for construct validity using Cronbach's alpha and for convergent and discriminant validity. The internal consistency of the model's constructs was also determined using an exploratory factor analysis using the principal components method. Positive and significant correlations were found between perceived fairness, job satisfaction, support for innovation and trust, as well as negative and significant correlations between these constructs and job desertion. The Covariance-Based Structural Equation Method (CB-SEM) was also used to determine causality conditions between the variables of perceived justice, job satisfaction, support for innovation, and trust concerning job dropout. It was found that organisational justice and job satisfaction predict a negative effect on job dropout. However, this effect was not pessimistic about the variables of trust and support for innovation. We conclude the importance of considering actions that promote workers' subjective well-being and on a series of recommendations for best practice management. RESUMEN Los empleados juegan un papel vital en los resultados de las empresas, es por ello que el estudio de elementos del comportamiento y clima de la empresa es necesario para la retención del talento humano. Este estudio tiene como objetivo identificar la influencia de la equidad percibida, la satisfacción laboral, el apoyo a la innovación y la confianza en la rotación de empleados y la relación entre estas variables. Para lograr este objetivo se realizó un diseño metodológico cuantitativo. Se administró un cuestionario a 555 empleados de una empresa de la industria de alimentos en el noroeste de México. Este instrumento fue validado para la validez de constructo mediante el alfa de Cronbach y para la validez convergente y discriminante. La consistencia interna de los constructos del modelo también se determinó mediante un análisis factorial exploratorio utilizando el método de componentes principales. Se encontraron correlaciones positivas y significativas entre la equidad percibida, la satisfacción laboral, el apoyo a la innovación y la confianza, así como correlaciones negativas y significativas entre estos constructos y la deserción laboral. También se utilizó el Método de Ecuaciones Estructurales Basadas en Covarianza (CB-SEM) para determinar las condiciones de causalidad entre las variables justicia percibida, satisfacción laboral, apoyo a la innovación y confianza en la deserción laboral. Se encontró que la justicia organizacional y la satisfacción laboral predicen un efecto negativo en la deserción laboral. Sin embargo, este efecto no fue pesimista sobre las variables de confianza y apoyo a la innovación. Concluimos la importancia de considerar acciones que promuevan el bienestar subjetivo de los trabajadores y sobre una serie de recomendaciones para la gestión de buenas prácticas.
Journal of Legal, Ethical and Regulatory Issues
Keywords: Organisational justice; Job satisfaction; Attrition; Trust; Innovation; Sistemas